Perceived stress score among doctors serving at various government and private hospitals in Faisalabad - Nazia Nazir; Hafiz Amjad Hussain; Umair Ahmed; Ahmad Ayaz Sabri; Nazir Ahmad; Amna Gulam Rasool (Journal of the Pakistan Medical Association, 2021)
Objective: To analyze the prevalence of stress among doctors serving at various Government and private hospitals in Faisalabad. Methods: The cross-sectional study was conducted at Allied hospital, DHQ hospital, Government General Hospital and independent hospital Faisalabad, from July to December 2019. The study comprised doctors in service for at least one year, who volunteered to fill out the Perceived Stress Scale Questionnaire (PSS-14), excluding house officers and the doctors on administrative posts. Demographic features and job factors were taken as independent variables and perceived stress score was taken as the dependent variable. SPSS-20 was used for the determination of mean perceived stress score, standard deviation values, analysis of variance (ANOVA) and Pearson correlation analysis (R-values) . Results: Out of total 162 respondents, female doctors (n=75, 46.3%) were found to have significantly higher (p < 0.05) perceived stress scores (mean PSS = 27.56, SD = 8.305) as compared to male doctors (n=87, 53.7%, mean PSS = 24.82, SD = 7.823). There was a negative correlation of doctors’ age (R-value = -0.246, p-value = 0.002), number of years in job (R-value =-0.187, p-value 0.017) and number of children (R-value =-0.178, p-value = 0.023), with the perceived stress scores. Stress score was found significantly lower for doctors who managed to usually get time-out for relaxation (p < 0.01) and do private practice (p < 0.05). The effect of doctor’s marital status, type of specialty and residence was not found statistically significant. Continuous...